Envisioning postmortal futures: six archetypes on future societal approaches to seeking immortality. - Hurtado Hurtado, Joshua (Mortality, 2024)
Death is a core feature of the human experience and a main driver of civilisational endeavours. Attempts to transcend it have propelled the emergence of a postmortal society in the twenty-first century, where people have looked into the various possibilities to achieve some form of immortality. While research on the postmortal society and the futures of death have examined the social practices for death transcendence in the present and outlined some possibilities for the future, discussion remains rare on the various ways this quest for immortality can reconfigure societal worldviews, institutions and practices. By analysing data obtained from a literature review on the sociology of immortality and the futures of death, an expert roundtable and 18 semi-structured interviews, six archetypal postmortal futures were developed: Digital Recreation, Transhumanism, Memorialisation-based Postmortality, Biological Life-extension, Back to the Earthly Realm, and Unity with the Cosmos. This article argues that paradigmatic societal changes shape the immortality-seeking practices that emerge in a given spatiotemporal context. The future-oriented perspective contributes to the literature on the sociology of immortality by discussing both how some postmortal futures may increase inequalities in the pursuit of immortality and how these futures, as a whole, represent future societal attitudes towards death.